Maintaining procedural skills for academic emergency medicine faculty: A needs assessment. Issue 4 (23rd November 2021) - Clyne, Brian; Barber Doucet, Hannah; Brown, Linda; Musits, Andrew; Jacobs, Elizabeth; Merritt, Christopher; Merritt, Rory; Allister, Lauren; Petrone, Gianna; Musisca, Nicholas; Smith, Jessica L.; Baird, Janette; et al.
Abstract: Background: Emergency physicians require competence performing critical and routine procedures. The clinical practice of emergency medicine (EM) alone may be insufficient for the acquisition and maintenance of skills. Prior studies suggest the presence of trainees in academic settings and/or the low frequency of procedures increase the risk of skills attrition among faculty. We sought to develop a valid needs assessment survey to inform a faculty procedural skills (FPS) maintenance curriculum. Methods: A Web‐based FPS survey was designed to assess experiences performing procedures, self‐reported confidence with procedures, and learning preferences for skills maintenance. The survey was administered at a large academic department of EM. Responses were analyzed to determine survey construct validity, faculty attitudes about procedural attrition, and preferred learning methods. Results: Among EM faculty, confidence was significantly higher for common versus uncommon procedures (p < 0.001). EM faculty respondents reported significantly greater confidence than pediatric EM (PEM) faculty for both common adult procedures (EM mean = 3.7 [±0.3], PEM = 3.0 [±0.4], p < 0.001), and uncommon adult procedures (EM = 2.7 [±0.4], PEM = 2.1 [±0.5], p < 0.001). PEM faculty reported significantly greater confidence with pediatric procedures than EM faculty (PEM mean [±SD] = 3.5 [±0.8], EM = 2.2 [±0.8], p < 0.001). Nearly all faculty (93% [52/56]) agreed that procedural attrition is a concerning problem, and 80% (44/56) had personally experienced it. The most preferred learning methods were task trainers and simulation. Faculty preferred learning environments with faculty peers (91%) over mixed groups with trainees (50%). Conclusions: Significant differences in procedural skills confidence between common and uncommon procedures, and between EM and PEM faculty, indicate that the FPS survey displayed appropriate construct validity. The finding that skills attrition is prevalent among EM and PEM faculty highlights the need for skill maintenance programming, preferably in peer groups employing task trainers and simulation.